2021
DOI: 10.1186/s12870-021-02965-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome regulation of carotenoids in five flesh-colored watermelons (Citrullus lanatus)

Abstract: Background Fruit flesh color in watermelon (Citrullus lanatus) is a great index for evaluating the appearance quality and a key contributor influencing consumers’ preferences. But the molecular mechanism of this intricate trait remains largely unknown. Here, the carotenoids and transcriptome dynamics during the fruit development of cultivated watermelon with five different flesh colors were analyzed. Results A total of 13 carotenoids and 16,781 dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 56 publications
1
8
0
5
Order By: Relevance
“…In this study, the flesh color inheritance analysis using the F 2 and F 3 segregation populations produced from the cross between the canary yellow (HSH-F) and white (Sanbai) flesh lines obtained a 3:1 segregation ratio of canary yellow/white flesh ( Table 1 ). Consistent with previous studies, the canary yellow flesh contained abundant xanthophyll, whereas white flesh watermelon accumulated trace carotenoids ( Figure 1B and Supplementary Table S2 ) ( Bang et al., 2010 ; Zhao et al., 2013 ; Lv et al., 2015 ; Diao et al., 2021 ; Yuan et al., 2021 ). To examine whether the white flesh in Sanbai resulted from the malfunction of the canary yellow flesh locus, we crossed an orange flesh line (CG149), which accumulated massive carotene but lacked xanthophyll ( Figure 1B and Supplementary Table S2 ), with the canary yellow (HSH-F) and white flesh (Sanbai) lines.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the flesh color inheritance analysis using the F 2 and F 3 segregation populations produced from the cross between the canary yellow (HSH-F) and white (Sanbai) flesh lines obtained a 3:1 segregation ratio of canary yellow/white flesh ( Table 1 ). Consistent with previous studies, the canary yellow flesh contained abundant xanthophyll, whereas white flesh watermelon accumulated trace carotenoids ( Figure 1B and Supplementary Table S2 ) ( Bang et al., 2010 ; Zhao et al., 2013 ; Lv et al., 2015 ; Diao et al., 2021 ; Yuan et al., 2021 ). To examine whether the white flesh in Sanbai resulted from the malfunction of the canary yellow flesh locus, we crossed an orange flesh line (CG149), which accumulated massive carotene but lacked xanthophyll ( Figure 1B and Supplementary Table S2 ), with the canary yellow (HSH-F) and white flesh (Sanbai) lines.…”
Section: Discussionsupporting
confidence: 90%
“…A high transcript abundance of LCYB / LCYE was associated with the high accumulation of carotene in fruits ( Lu et al., 2006 ; Ampomah-Dwamena et al., 2009 ; Liu et al., 2015 ). In watermelon, the production of violaxanthin and lutein in yellow flesh was positively correlated with the expression levels of CHYB and ZEP ( Lv et al., 2015 ; Yuan et al., 2021 ). In addition, the modulation of carotenogenic enzymes and the regulation of chromoplast biogenesis, development, and differentiation have been demonstrated to strongly affect carotenoid accumulation ( Yuan et al., 2015 ; Sun et al., 2018 ; Feder et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…KEGG enrichment analysis and NR annotation showed that, there are 27 structural genes participated in carotenoid metabolic pathway among the four combinations (LY vs. W, Y vs. W, O vs. W, OR vs. W), and the sweetpotato carotenoid metabolic pathway were mapped ( Figure 3 ). The pathway was constructed based on KEGG and references ( Suematsu et al., 2020 ; Xu et al., 2021 ; Yuan et al., 2021 ; KEGG, 2022 ). Of which 10 DEGs namely Or (1), CRTISO (1), CYP97B2 (1), CHYB (1), ZEP (2), NSY (1) and DWARF27 (3) were playing major role in carotenoid biosynthesis pathway and 17 DEGs namely CCD1 (8), CCD4 (1), CCD7 (1), NCED (4) and CYP707A (3) were related to carotenoid degradation pathway.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, several transcription factors that regulate and control the carotenoid metabolic pathway have been identified in several crop species ( Ampomah-Dwamena et al., 2019 ; Yuan et al., 2021 ). In present study, we performed WGCNA to identify transcription factors that coordinately regulate the biosynthesis and accumulation of carotenoids.…”
Section: Discussionmentioning
confidence: 99%
“…The genes designated as Cla018767 , Cla018768 , Cla018769, Cla018770, and Cla018771 were linked to controlling red-flesh color development in watermelon for being involved in lycopene biosynthesis ( Li et al, 2020 ). The genes Cla003760 and Cla021635 conferred yellow flesh color development ( Yuan et al, 2021 ). Carotenoid metabolic pathway genes namely: ClPSY1 ( Cla009122 ), ClZDS ( Cla003751 ), ClNCED-7 ( Cla005404 ), ClCRTISO ( Cla017593 ), ClCHYB ( Cla006149 ), ClLCYB ( Cla005011 ), ClPDS ( Cla010898 ), ClNCED-1 ( Cla009779 ), and ClCHXE ( Cla011420 ) are involved in the development of white and pale-yellow fruit flesh color of watermelon (Wang et al, 2021).…”
Section: Genetic Analysis Of Fruit Quality In Sweet Watermelonmentioning
confidence: 99%